PENGARUH DIGITALISASI TAHSIN DAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL ASSESMENT SISWA PADA MADRASAH - Ramli, Syahrur; Lainah, Lainah; Sesmiarni, Zulfani (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
Abstract This study analyzes extracurricular learning in MTsN 7 Lima Puluh Kota developed by applying digitalization of differentiated learning. The extracurricular concept uses media, facilities and infrastructure of labor computers and projectors with differentiated learning using digital tarteel applications. The use of the tarteel application will certainly have an impact on the final assessment results of eskul tahsin activities. This research is a type of experimental quantitative research. The variable X1 in this study is the digitization of tahsin, variable X2 is differentiated learning and variable Y is the result of tahsin assessment. The population and sample are 86 students of grade VII MTsN 7 Lima Puluh Kota of West Sumatra Province for the 2023/2024 academic year. Quantitative assessment data is obtained through pre-test and post-test. The instrument used is a questionnaire. The results of research through data testing showed that the influence of digital tahsin as much as 36% on the results of tahsin assessment. The effect of tahsin learning differentiated by 6% on the results of tahsin assessment. The results of the R square coefficient value show the influence of the two variables on Y by 0.6 or 60% of the influence of differentiated tahsin digital on the results of the assessment of tahsin students grade VII MTsN 7 Lima Puluh Kota. Keywords: Digital Tahsin; Differentiated Learning; Learning Assessment